Effect of Electroacupuncture at Baihui and Shenting on Cognitive Function in Cerebral Ischemia-reperfusion Injured Rats - Yongmei YOU; Yijing JIANG; Zhicheng LIN; Zengtu ZHAN; Jun WANG; Wei WEI; Shanli YANG (康复学报)
Objective:To observe the effect of electroacupuncture (EA) at Baihui and Shenting on cognitive function in rats after cerebral ischmeia-reperfusion (IR) injury, and explore the possible mechanism.Methods:A total of 111 male adult SD rats weighting (300±20) g were selected and randomly divided into the sham operation group (n=36) and the operation group (n=75). The common carotid artery, internal carotid artery and external carotid artery of rats in the sham-operation group were separated after anesthesia without ligation or thread insertion. The left middle cerebral arteries of rats in the operation group were occluded and reperfused by Zea Longa sutured-occluted method. Neurobehavioral score and cognitive impairment screening were performed on rats with Zea Longa score and Barnes maze test at two hours after surgery. The 72 rats meeting the inclusion criteria were randomly divided into model group (n=36) and electroacupuncture group (n=36). Two hours after the operation, the rats in the EA group were acupunctured at Baihui and Shenting. In the model group, expect that electroacupuncture was not used, the rest of the process was the same as that in the EA group. The changes in cognitive function of the rats were evaluated with Barnes maze 1, 7 days after cerebral ischmeia-reperfusion. The infarct volume was determined using TTC staining at 1, 7 days after surgery. In addition, Iba1 positive cells were used as markers of microglias/macrophages polarization. The polarization of microglial/macrophages in the hippocampus was observed by immunohistochemistry 1, 7 days after surgery in each group. The expression of MHCII(M1 microglia/macrophage marker protein) and Arg-1(M2 microglia/macrophage marker protein) in the hippocampus of rats were detected by Western blot 1, 7 days after surgery. The expression of TNF-α, IL-1β(M1 microglia/macrophage marker immunocytokines) and IL-10, TGF-β(M2 microglia/macrophage marker immunocytokines) in the hippocampus of rats were detected by ELISA 1, 7 days after surgery.Results:①No neurologic impairment was observed in the sham operation group; compared with the sham operation group at two hours after surgery, the neurobehavioral scores of the model group and the EA group were significantly increased (P< 0.05), Barnes maze escape incubation period was significantly prolonged (P< 0.05), and the number of entering the wrong hole was significantly increased (P< 0.05); at one day after surgery, there was no significant difference in Barnes maze escape latency time and number of entering the wrong hole between the EA group and the model group (P> 0.05); however, at seven days after surgery, compared with the model group, Barnes maze escape latency time and number of entering the wrong hole in the EA group were significantly reduced (P< 0.05). ②No TTC staining could be observed in the sham operation group at each point. There was no significant difference in cerebral infarction volume between the EA group and the model group at one day after surgery (P> 0.05), and the reduction of cerebral infarction volume in the EA group was better than that in the model group at seven days after surgery (P< 0.05). ③At 1, 7 days after surgery, the positive expression rate of Iba1 in the EA group and the model group was significantly higher than that in the sham operation group (P< 0.05), and there was no significant difference in the positive expression rate of Iba1 between the EA group and the model group (P> 0.05). ④At one day after surgery, the protein expression of Iba1, MHCII, TNF-α and IL-1β in the EA group and the model group were significantly increased compared with the sham operation group (P< 0.05), there were significant differences in the protein expression of Arg-1, IL-10 and TGF-β in the EA group and the model group compared with the sham operation group (P< 0.05), and there was no significant difference in the protein expression of Iba1, MHCII, TNF-α, IL-1β, Arg-1, IL-10 and TGF-β between the EA group and the model group (P> 0.05). At seven days after surgery, the protein expressions of MHCII, TNF-α and IL-1β in the EA group and the sham operation group were significantly decreased compared with the model group (P< 0.05), while the protein expressions of Arg-1, IL-10 and TGF-β in the EA group were significantly increased compared with the model group and the sham operation group (P< 0.05).Conclusion:Electroacupuncture at Baihui and Shenting can effectively improve the cognitive function of rats with cerebral ischemia reperfusion injury. The mechanism may inhibit the M1 polarization of microglia/macrophages, promote the M2 polarization, regulate the neuroinflammatory response to a certain extent, and promote the recovery of cognitive function.